FRI0205 Relationship between Anti-Citrullinated Protein Antibody Status and Response To Abatacept or Anti-Tumour Necrosis Factor Therapy in Patients with Rheumatoid Arthritis: A US National Observational Study. (15th July 2016) - Harrold, L.R.; Litman, H.J.; Connolly, S.E.; Kelly, S.; Hua, W.; Alemao, E.; Rosenblatt, L.; Rebello, S.; Kremer, J.
Abstract : Background: Anti-citrullinated protein antibodies (ACPA) are associated with more severe, erosive rheumatoid arthritis (RA), but the extent to which ACPA status predicts response to therapy is not known. 1, 2 Objectives: To evaluate in a real-world, observational RA cohort whether baseline ACPA status is associated with response to biologics among patients with RA. Methods: Using the Corrona RA registry, we identified patients with RA who initiated abatacept (ABA) or a tumour necrosis factor-alpha inhibitor (TNFi) between June 2002 and January 2015, had a follow-up visit 6 months (±3 months) after initiation and anti-cyclic citrullinated peptide (anti-CCP [a surrogate of ACPA]) measured at or prior to initiation. Anti-CCP positivity was defined as anti-CCP ≥20 U/mL. The primary outcome was mean change from baseline in Clinical Disease Activity Index (CDAI) at 6 months. Secondary outcomes at 6 months included: 1) achievement of low disease activity (LDA; CDAI ≤10) among those with moderate or high disease activity who initiated treatment; 2) achievement of remission (CDAI ≤2.8) in those with low, moderate or high disease activity who initiated treatment; 3) Minimally Important Clinical Difference (MCID) in CDAI; and 4) modified ACR20/50/70. Unadjusted and adjusted linear and logistic analyses were performed based on anti-CCP status (positive [+] vs negative [–]). Results: 566 patients initiated ABA: 204 (36.0%) were anti-CCP– and 362 (64.0%) anti-CCP+. There were no differences by CCP status for age (mean 57–58 years), disease duration (median 7 years) or prior biologic use (0, 1 or ≥2 prior); however, median baseline CDAI was greater in anti-CCP– vs anti-CCP+ patients (21 vs 19, p=0.035). 1715 patients initiated a TNFi: 602 (35.1%) were anti-CCP– and 1113 (64.9%) anti-CCP+. There were no differences by CCP status for age (mean 55–56 years), prior biologic use or median baseline CDAI; however, median disease duration was greater in anti-CCP+ vs anti-CCP– patients (4 vs 3 years, p=0.021). In adjusted analyses, anti-CCP+ ABA initiators had a mean (SE) change in CDAI of –8.5 (0.6) vs –4.1 (0.8) for anti-CCP– (p<0.001); in TNFi initiators, this was –7.4 (0.3) vs –6.4 (0.4) (p=0.071). In the multivariate model for secondary outcomes, the magnitude of response was greater in anti-CCP+ vs anti-CCP– ABA initiators. Outcomes did not differ by anti-CCP status in TNFi initiators (Figure ). Conclusions: In a clinical practice setting, anti-CCP positivity was associated with a differential treatment response to abatacept, but not TNFis. These real-world data suggest that anti-CCP+ patients with RA show incremental improvements in response while receiving abatacept therapy compared with anti-CCP– patients. References: Lv Q, et al. PLoS One 2014;9:e89442. Sokolove J, et al. Ann Rheum Dis 2015; doi:10.1136/annrheumdis-2015-207942. Disclosure of Interest: L. R. Harrold Grant/research support from: Pfizer, H. J. Litman Employee of: Corrona, S. E. Connolly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Kelly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, W. Hua Employee of: Corrona, E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, L. Rosenblatt Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Rebello Employee of: Corrona, J. Kremer Shareholder of: Corrona, Grant/research support from: AbbVie, Bristol-Myers Squibb, Genentech, Lilly, Novartis, Pfizer, Employee of: Corrona, Speakers bureau: Genentech (non-branded talks only)